Kosmopolitanisme dan Transmisi Keilmuan Pada Kejayaan Intelektual Dinasti âAbbÃ¢sÃ®yah - Mardiana, Septa (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
The âAbbasid intellectual heyday was a social condition that was built up of cosmopolitanism of Islamic society. Cosmopolitanism means recognizing the diversity of identity, emphasizing the dynamic character of the various groups, and responding the potential for creating new cultural combinations. The âAbbasid Dynasty facilitated inter-cultural assimilation process, so that the intellectual tradition developed so rapidly. The intellectual triumph was established because of the cultural hybrid of âfriendlyâ and âunfriendlyâ cultures that interacted symmetric-ally. Elements of cultural authenticity brought by immigrants experienced universalization and thus recognized by other tribes. One of the ways of the universalization was through the transmission of knowledge in the administration of education in classical educational institutions. The cosmopolitanism of âAbbas-id Islamic society made the transmission process conducted in various Islamic educational institutions rich and diverse. In addition, the impact of cultural assimilation adopted by âAbbasid society contributed to cultural diffusion, one of which was the transmission of knowledge.